2017: The Quincentennial Celebration of the Reformation in an Age of Secularization and Religious Pluralism. Issue 1 (March 2016) - Lehmann, Hartmut
Abstract: In the last days of October 1517 Martin Luther finished a series of theological theses in which he argued that selling indulgences was theologically wrong; in fact, untenable. Protestants consider Luther's initiative the beginning of the Reformation. But how should we celebrate the memory of these events that took place 500 years ago? What is the lasting value of Luther's message in our time, in an age of secularization and religious pluralism?